The XX sex chromosome complement in mice is associated with increased spontaneous lupus compared with XY. Issue 8 (12th May 2012) - Sasidhar, Manda V; Itoh, Noriko; Gold, Stefan M; Lawson, Gregory W; Voskuhl, Rhonda R
Abstract : Objectives: Many autoimmune diseases are characterised by a female predominance. This may be caused by sex hormones, sex chromosomes or both. This report uses a transgenic mouse model to investigate how sex chromosome complement, not confounded by differences in gonadal type, might contribute to lupus pathogenesis. Methods: Transgenic NZM2328 mice were created by deletion of the Sry gene from the Y chromosome, thereby separating genetic from gonadal sex. Survival, renal histopathology and markers of immune activation were compared in mice carrying the XX versus the XY − sex chromosome complement, with each genotype being ovary bearing. Results: Mice with XX sex chromosome complement compared with XY − exhibited poorer survival rates and increased kidney pathology. Splenic T lymphocytes from XX mice demonstrated upregulated X-linked CD40 ligand expression and higher levels of activation markers ex vivo. Increased MMP, TGF and IL-13 production was found, while IL-2 was lower in XX mice. An accumulation of splenic follicular B cells and peritoneal marginal zone B cells was observed, coupled with upregulated costimulatory marker expression on B cells in XX mice. Conclusion: These data show that the XX sex chromosome complement, compared with XY −, is associated with accelerated spontaneous lupus.